A Peaceful Jihad - Lukens-Bull, R. author. aut Link
XVII, 152 p.
Keywords: Based on extensive ethnographic research, this book examines how the Islamic community in Java, Indonesia, is actively negotiating both modernity and tradition in the contexts of nation-building, globalisation, and a supposed clash of civilizations. The pesantren community, so-called because it is centered around an educational institution called the pesantren, uses education as a central arena for dealing with globalization and the construction and maintenance of an Indonesian Islamic identity. However, the community's efforts to wrestle with these issues extend beyond education into the public sphere in general and specifically in the area of leadership and politics. The case material is used to understand Muslim strategies and responses to civilizational contact and conflict. Scholars, educated readers, and advanced undergraduates interested in Islam, religious education, the construction of religious identity in the context of national politics and globalization will find this work useful.